Circulating Soluble CD163 is Associated with Steatohepatitis and Advanced Fibrosis in Nonalcoholic Fatty Liver Disease. Issue 10 (October 2015) - Mueller, Jessica L; Feeney, Eoin R; Zheng, Hui; Misdraji, Joseph; Kruger, Annie J; Alatrakchi, Nadia; King, Lindsay Y; Gelrud, Louis; Corey, Kathleen E; Chung, Raymond T
Abstract : OBJECTIVES: : Soluble CD163 (sCD163), a marker of Kupffer cell activation detectable in serum, correlates with inflammation and fibrosis in chronic viral hepatitis, but its role in nonalcoholic fatty liver disease is unknown. We hypothesized that sCD163 would correlate with nonalcoholic fatty liver disease activity and fibrosis. METHODS: : Liver biopsies and serum were obtained from 145 obese subjects undergoing gastric bypass surgery. Subjects were divided into four groups based on fibrosis stage and nonalcoholic fatty liver disease activity score (NAS); Group 1: F0, NAS=0; Group 2: F<2, 0<NAS<5; Group 3: NAS≥5, F<3; or Group 4: F≥3, any NAS. Serum sCD163 and the monocyte/macrophage marker sCD14 were measured by enzyme‐linked immunosorbent assay. Relationships between sCD163, sCD14, fibrosis stage, and NAS were examined. Area under the receiver operating charateristic for the diagnosis of nonalcoholic steatohepatitis based on the Clinical Research Network definition was calculated. RESULTS: : sCD163 increased with progressive liver histology, with lowest values in normal histology and highest levels in those with nonalcoholic steatohepatitis and advanced fibrosis (Group 1: 552 ng/ml, Group 2: 721 ng/ml, Group 3: 803 ng/ml, and Group 4:1, 031; P =0.001). sCD14 also differed significantly across groups (Group 1: 1, 877 ng/ml, Group 2: 1632 ng/ml, Group 3: 1, 706 ng/ml, and Group 4: 2111; P =0.008, respectively). sCD163 correlated with steatosis grade ( P <0.001), lobular inflammation ( P =0.033), and hepatocyte ballooning ( P <0.001). In a multivariable ordered logistic regression model, there was a significant association between every 100 ng/ml increase in sCD163 and higher fibrosis stage, with an odds ratio of 1.16 (95% confidence interval 1.02–1.31), P =0.020. The odds ratios of the association between every 100 ng/ml increase in sCD163 and higher NAS was 1.17 (95% confidence interval 1.04–1.32), P =0.010. A sCD163‐based predictive score demonstrated an area under the receiver operating charateristic of 0.70 (95% confidence interval: 0.58–0.82) for the diagnosis of nonalcoholic steatohepatitis. Soluble CD14 did not correlate with fibrosis stage or NAS. CONCLUSIONS: : In obese subjects, serum sCD163, but not sCD14, correlated with fibrosis stage and NAS. These data support a role for activated Kupffer cells in the pathogenesis of nonalcoholic steatohepatitis and fibrosis, and suggest potential clinical utility for assessment of sCD163 levels.